Understanding extracellular vesicle biology for the development of bioinspired nanotechnology platforms - Bonner, SE (2022)
Extracellular vesicles (EVs) are membranous nanoparticles released by cells that are important mediators of intercellular communication via transfer of their cargoes to recipient cells. For this reason, EVs have been harnessed as a novel targeted therapeutic delivery platform. However, EV research faces numerous challenges that need to be addressed if their potential as therapeutic devices is to be fully realised.